Action of linezolid or vancomycin on biofilms in ventriculoperitoneal shunts in vitro - Bayston, Roger; Ullas, Gautham; Ashraf, Waheed (American Society for Microbiology, 2012)
Cerebrospinal fluid (CSF) shunts used to treat hydrocephalus have an overall infection rate of about 10% of operations. The commonest causative bacteria are Staphylococcus epidermidis, followed by Staphylococcus aureus and enterococci. Major difficulties are encountered with nonsurgical treatment due to biofilm development in the shunt tubing and inability to achieve sufficiently high CSF drug levels by intravenous administration. Recently, three cases of S. epidermidis CSF shunt infection have been treated by intravenous linezolid without surgical shunt removal, and we therefore investigated vancomycin and linezolid against biofilms of these bacteria in vitro. A continuous-perfusion model of shunt catheter biofilms was used to establish mature (1-week) biofilms of Staphylococcus aureus, Staphylococcus epidermidis (both methicillin resistant [MRSA and MRSE]), Enterococcus faecalis, and Enterococcus faecium. They were then “treated” with either vancomycin or linezolid in concentrations achievable in CSF for 14 days. The biofilms were then monitored for 1 week for eradication and for regrowth. Enterococcal biofilms were not eradicated by either vancomycin or linezolid. Staphylococcal biofilms were eradicated by both antibiotics after 2 days and did not regrow. No resistance was seen. Linezolid at concentrations achievable by intravenous or oral administration was able to eradicate biofilms of both S. epidermidis (MRSE) and S. aureus (MRSA). Neither vancomycin at concentrations achievable by intrathecal administration nor linezolid was able to eradicate enterococcal biofilms. It is hoped that these in vitro results will stimulate further clinical trials with linezolid, avoiding surgical shunt removal.